Evaluation of fouling and chemical cleaning of reverse osmosis membrane after treatment of geothermal water - Zaid, Aseel; Jarma, Yakubu Abdullahi; Ahmed Senan, Islam Rashad; Karaoğlu, Aslı; Cihanoğlu, Aydın; Baba, Alper; Kabay, Nalan (Frontiers in Membrane Science and Technology, 2025)
In this study, high mineral scaling propensity geothermal water was treated using a FilmTech BW30-2540 reverse osmosis (RO) membrane, integrated into a mini-pilot scale membrane test unit installed at a geothermal heating center. The study was conducted in eight cycles by monitoring membrane fouling via membrane flux decline. Firstly, the geothermal water coming from the source at approximately 80°C was taken into holding tanks and allowed to reach approximately room temperature (25°C). Then, the geothermal water that reached this temperature was used in the system. The fouling degree was compared to the initial permeability of the virgin membrane. After each treatment cycle, the membrane’s permeability was evaluated both before and after acid cleaning. Permeability testing was conducted using RO permeate as the feed, under pressures ranging from 8 to 30 bar, with 2-bar increments. The geothermal water treatment was performed at a constant pressure of 15 bar, with a water recovery maintained at approximately 50%. Prior to each permeability test, the membrane underwent a 45-min wash with citric acid, followed by a rinse with RO permeate. During the first five cycles, citric acid was used at a concentration of 1000 mg/L, achieving a flux recovery of 86.6% by the fifth cycle. In the subsequent three cycles, the citric acid concentration was increased to 4000 mg/L, resulting in a flux recovery of 63.4% by the eighth cycle. The study concluded that scale formation on the membrane surface intensified as the number of cycles increased.